Decomposition behavior in the early-stage oxidation of Sm2Co17-type magnets - Zhang, Yong (2022)
Irredeemable magnetic loss caused by oxidation remains a critical concern for the application of Sm2Co17-type permanent magnets. Herein, oxygen induced decomposition in the early-stage oxidation of a Sm(CobalFe23.5Cu4.9Zr1.7)7.5 magnet is studied using aberration-corrected TEM. Upon oxygen penetration along the 1:3R Z-plates, the 1:5H cell boundaries are decomposed into separate Sm and Co(Fe) lamellae with thicknesses of ~5 nm. Subsequently, the Fe-rich 2:17R cells are decomposed into similar metal lamellae. Besides the normal hexagonal stacking, the Sm lamellae also exhibit a twinned face-centered cubic (FCC) structure. The decomposed Co(Fe) lamellae and Cu particles are FCC-structured. The nano-twinned Cu particles are sparsely distributed. Interestingly, the closely-packed planes of these metal lamellae tend to align with the {0001}2:17R plane. The metal lamellae enriched with oxygen interstitials finally turn into nano-oxides by oxidation. This work offers in-depth insights into the initial oxidation behavior of alloys.